Problems with the identification of 'problematic' cannabis use: Examining the issues of frequency, quantity, and drug use environment - Asbridge, M.; Duff, Cameron; Marsh, D.; Erickson, P. (2014)
© 2014 S. Karger AG, Basel. Considerable recent attention has focused on how harmful or problematic cannabis use is defined and understood in the literature and put to use in clinical practice. The aim of the current study is to review conceptual and measurement shortcomings in the identification of problematic cannabis use, drawing on the WHO ASSIST instrument for specific examples. Three issues with the current approach are debated and discussed: (1) the identification of problematic cannabis use disproportionately relies on measures of the frequency of cannabis consumption rather than the harms experienced; (2) the quantity consumed on a typical day is not considered when assessing problematic use, and (3) screening tools for problematic use employ a 'one-size-fits-all approach' and fail to reflect on the drug use context (networks and environment). Our commentary tackles each issue, with a review of relevant literature coupled with analyses of two Canadian data sources-a representative sample of the Canadian adult population and a smaller sample of adult, regular, long-term cannabis users from four Canadian cities-to further articulate each point. This article concludes with a discussion of appropriate treatment interventions and approaches to reduce cannabis-related harms, and offers suggested changes to improve the measurement of problematic cannabis use.